Screening of Potential Fungi from Polluted Soil for Copper Bioremediation - Ong, Ghim Hock (2016)
Copper (Cu) naturally exists in the environment but excess Cu in the environment is harmful to human beings. In order to control Cu pollution, bioremediation using fungi can be applied. The objective of this study was to screen out potential fungal species that can be used for bioremediation of copper from soil. The soil samples were collected from a steel factory called Amsteel mill in Klang. The fungi were isolated from the soil samples using Rose Bengal agar (RBA) and subsequently cultured on Potato Dextrose agar (PDA) to obtain pure cultures. The fungal isolates were subjected to toxicity testing using copper sulphate concentrations up to 300 ppm. Fungi were identified macroscopically and microscopically. The results showed that 3 fungal species Fusarium solani, Aspergillus niger and Aspergillus tamarii were able to tolerate and grow in the presence of copper, hence making them potential bioremediation agents.